If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4w + -8) + 2w = 64 Reorder the terms: (-8 + 4w) + 2w = 64 Remove parenthesis around (-8 + 4w) -8 + 4w + 2w = 64 Combine like terms: 4w + 2w = 6w -8 + 6w = 64 Solving -8 + 6w = 64 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6w = 64 + 8 Combine like terms: -8 + 8 = 0 0 + 6w = 64 + 8 6w = 64 + 8 Combine like terms: 64 + 8 = 72 6w = 72 Divide each side by '6'. w = 12 Simplifying w = 12
| X+-3=18 | | 12*7+908p=908 | | 0.1(100-x)=0.35x | | 3sin(2x)+3sinx=0 | | 10.1666667=a | | 742.61=2*3.14*256+2*3.14*16*h | | -6.4(4x+6)-2.1(2x-4)= | | 10.1666667= | | 9a-2b= | | 2m+1*-5= | | 0.7=0.861 | | (x*12)+x=9646 | | 7+5*8+78u=12y+4z | | -6.25=0.6c | | x+0.15=2500 | | 3(2n+5)=9(3n+7)+8 | | l+l+0.25l=135 | | -1.3g+1.9=11.1 | | 6(3s+7)=276 | | 3(2t+-1)+2t=6-t | | 6(5m+3)=3(3m+5) | | fu*7+76=12y+9087 | | p-3=114 | | 5x-2-(-3x+4)= | | 6r-9=7+4r | | 5x+7-3(2x+9)=2(x-8)-13 | | 2m+1*5= | | 4(2x+4)-20=12 | | 2(a-8)=10 | | r-ll/3=-7 | | -3(5t-4)+5t=7t-7 | | 2w+4-(3w+6)= |